Prove: \dfraf{cos³A + sin³A}{cosA + sinA} = \frac{1}{2} (2 - sin2A)

Solution:

LHS

= \dfrac{cos³A + sin³A}{cosA + sinA}

= \dfrac{(cosA)^3 + (sinA)^3}{cosA + sinA}

Expand the numerator using the factorisation formula of (a³+b³)

= \dfrac{(cosA + sinA)(cos²A - sinAcosA + sin²A)}{(cosA + sinA)}

= cos²A - sinAcosA + sin²A

= (cos²A + sin²A) - sinAcosA

Use the identity of (cos²A + sin²A = 1)

$= (1- sinAcosA)$

Multiply and divide the expression by 2 to get closer to your RHS

= \dfrac{2}{2} × (1 - sinAcosA)

= \dfrac{1}{2} (2-2sinAcosA)

Use the formula of sin2A to contract the expression

= \dfrac{1}{2} (2-  sin2A)

RHS

See more solutions of Trigonometry: